2013
DOI: 10.1021/la401302p
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the Catalytic Activity of Porous Platinum Nanostructures

Abstract: The catalytic activity of porous platinum nanostructures, viz. platinum nanonets (PtNNs) and platinum nanoballs (PtNBs), synthesized by radiolysis were studied using two model reactions (i) electron transfer reaction between hexacyanoferrate (III) and sodium thiosulfate and (ii) the reduction of p-nitrophenol by sodium borohydride to p-aminophenol. The kinetic investigations were carried out for the platinum nanostructure-catalyzed reactions at different temperatures. The pseudofirst-order rate constant for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(50 citation statements)
references
References 58 publications
2
48
0
Order By: Relevance
“…For example, the assembly of chemically synthesized nanoparticles into network architectures has been proven to exhibit enhanced catalytic activity in comparison with the original mono dispersed Pt nanoparticles. [ 37,38 ] Despite of this enhancement, there is still a room to further improve the catalytic performance if the capping species can be removed from the Pt nanostructures. Although conventional thermal annealing can burn away the capping species from the assembled porous architectures, it can sinter the Pt nanoparticles and greatly decrease the porosity in the architectures.…”
Section: Application Of Porous Pt Csps In Solution-phase Heterogeneoumentioning
confidence: 99%
“…For example, the assembly of chemically synthesized nanoparticles into network architectures has been proven to exhibit enhanced catalytic activity in comparison with the original mono dispersed Pt nanoparticles. [ 37,38 ] Despite of this enhancement, there is still a room to further improve the catalytic performance if the capping species can be removed from the Pt nanostructures. Although conventional thermal annealing can burn away the capping species from the assembled porous architectures, it can sinter the Pt nanoparticles and greatly decrease the porosity in the architectures.…”
Section: Application Of Porous Pt Csps In Solution-phase Heterogeneoumentioning
confidence: 99%
“…It is easy to understand that hollow or porous Pd/Pt nanostructures are favorable to improve Pt utilization efficiency and enhance their catalytic activity due to their high surface-to-volume and surface permeability [25,26]. For example, Xia's group has demonstrated that the PdePt nanocages exhibit stronger catalytic activity and selectivity for the preferential oxidation of CO in excess hydrogen than Pd nanocubes and commercial Pt/C because of its alloy composition and hollow structure [27].…”
Section: Introductionmentioning
confidence: 99%
“…However, as conversion is made under stirring, O 2 dissolution inside solution appears gradually and leads to a weak oxidation of Cu according Eq. (7). This phenomenon explains why the platinum atomic percentage value is slightly superior to the maximal one.…”
Section: Copper-platinum Nanoparticlesmentioning
confidence: 90%
“…(3)) becomes negligeable but oxygen continues to react with accessible copper according to Eq. (7). It results in a break on the curve.…”
Section: Copper-platinum Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation